The Effect of Various Insecticide Active Ingredients on the Intensity of Pest Attacks on Red Pepper Plants (Capsicum annuum L.) - Dwi Rohmansah, Nandar; Zakka Alfarissy Nurrahman, Muhammad; Rona, Rona; Deden, Deden; Dukat, Dukat (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
Red Chili (Capsicum annuum L.) is an annuals of the eggplant family (Solanaceae). This plant comes from the American continent, precisely in the Peruvian area, and extends to other areas on the continent. The average consumption of red chili per capita of Indonesian people is 500 grams/year, 118,800 tons per year. Chili production in Indonesia has increased from year to year, in 2021 chili production reached 2,747,108 tons. Fruit caterpillars (helicoverpa armigera) are pests that often attack important plants in Indonesia. This pest usually attacks young fruits by making holes and eating them. An effort that farmers often make to control this pest is to use insecticides. Insecticides are chemicals that function to eradicate annoying insects. Common active ingredients applied for fruit caterpillar control are Chlorpyrifos, Chlorantraniliprol, Cipermethrin, Deltamethrin. This research was conducted in Ambit Village, Waled District, Cirebon Regency, West Java Province. The implementation time lasts for 3 months (July to September 2023). The method used in this study was Randomized Group Design (RGD) consisting of 5 treatments of various insecticide active ingredients and control (without treatment) repeated 5 times so that there were 25 experimental plots with treatment A (Chlorpyrifos), B (Chlorantraniliprol), C (Cipermethrin), D (Deltamethrin), and E (Control). The concentration of insecticide used is 2 ml / liter. The experimental results showed that the treatment of insecticide active ingredients had a real influence on the intensity of fruit caterpillar pest attacks (Helicoverpa amigera) and on other pests such as whitefly (Bemisia tabaci). Insecticides have no real effect on the intensity of chili plant disease attacks such as anthracnose disease (Colletotrichum gleosporioides). The insecticide applied also does not cause phytotoxicity to the growth of chili plants. The active ingredients of insecticides Chlorpyrifos, Chlorantraniliprol and Sipermethrin gave better results when compared to Deltrametrin and control insecticides. Thehighest harvest result was obtained from the treatment of the insecticide Chlorantraniliprol, as much as 10.31 kg/plot, or equivalent to 10.31 tons/ hectare.